Services marketing and management - Gilmore, Audrey (London ; Thousand Oaks, Calif. : Sage Publications, 2003)
Services Marketing and Management covers the core topics of services management in a concise and informative manner. The text: - provides an overview of the characteristics and underlying principles of delivering services in today's marketplace - places these underlying issues in the context of organisational frameworks and activities - discusses different services contexts including financial services, tourism, charities and museums.
Underlying themes -- Managing services -- Service management issues.
Includes bibliographical references and indexes.
Print version record.
eBooks on EBSCOhost
Keywords: Service industries -- Marketing; Service industries -- Management; Services (Industrie) -- Marketing; Services (Industrie) -- Gestion; BUSINESS & ECONOMICS -- Marketing -- General; BUSINESS & ECONOMICS -- Distribution; Service industries -- Management; Service industries -- Marketing; Dienstleistung; Dienstleistungsbetrieb; Management; Marketing; Dienstverlening; Marketing; Management